2003
DOI: 10.1103/physrevlett.90.063401
|View full text |Cite
|
Sign up to set email alerts
|

Time-Resolved Dynamics of Thermal Isomerization in Cesium-Halide Cluster Anions

Abstract: We have performed time-resolved studies of the dynamics of thermal isomerization occurring in certain cesium-halide cluster anions. Using a pump-probe technique, we have observed the repopulation of a photodepleted isomer within an ensemble as a function of time by monitoring the photoelectron spectrum. The rates of isomerization increase and the isomer lifetimes decrease as functions of temperature. The clusters undergo a gradual phase transition from solid-like to liquid-like states with liquid-like behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…[1][2][3][4] Several reports from our group [5][6][7] have used isomer-selective vibrational spectroscopies 8,9 to trace the major structural difference between isomers I and II at small sizes ͑n ഛ 8͒ to their local electron-binding motifs. Because several distinct structural arrangements of the water cluster anions are generally produced in typical ion sources, they are excellent model systems for understanding the molecular-level mechanics of how an excess electron is accommodated by well-characterized H-bonding networks.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Several reports from our group [5][6][7] have used isomer-selective vibrational spectroscopies 8,9 to trace the major structural difference between isomers I and II at small sizes ͑n ഛ 8͒ to their local electron-binding motifs. Because several distinct structural arrangements of the water cluster anions are generally produced in typical ion sources, they are excellent model systems for understanding the molecular-level mechanics of how an excess electron is accommodated by well-characterized H-bonding networks.…”
Section: Introductionmentioning
confidence: 99%
“…Besides specific cluster size effects on the transition size, thermal isomerization has been observed for small anionic CsX clusters (X = Cl, Br, or I) using photoelectron spectroscopy [13,14]. It was reported that at low temperatures cubiclike structures are most abundant while higher temperatures yield also ringlike isomers.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, this evaporation energy can be called vertical, although it includes some structural relaxation. The calculated vertical evaporation energies as a funtion of n yielded abrupt minima for sizes n = 5, 9,12,14,17,20,23,26,28. Evaporation of an MgO molecule from these clusters is relatively easier than from clusters of neighbor sizes.…”
Section: Most Intense Nmentioning
confidence: 96%
“…The method of gas aggregation from material evaporated in an oven can also be used to produce the clusters. A mass spectrum of (CsI) n Cs + clusters shows that the intensity peak corresponding to (CsI) 13 Cs + , that is [Cs 14 I 13 ] + , is very strong [2], and analogous studies of NaCl and CuBr clusters show that [Na 14 Cl 13 ] + and [Cu 14 Br 13 ] + also have enhanced abundances [3,4]. Figure 10.1.…”
Section: Nearly Stoichiometric Metal Halide Clustersmentioning
confidence: 99%
See 1 more Smart Citation